2014
DOI: 10.2217/imt.14.84
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Signaling, Tregs and Immune Modulation

Abstract: Foxp3+ Tregs are central regulators of immune tolerance. As dysregulated Treg responses contribute to disease pathogenesis, novel approaches to target the immunomodulatory functions of Tregs are currently under investigation. mTORC1 and mTORC2 are therapeutic targets of interest. Recent studies revealed that mTOR signaling impacts conventional T-cell homeostasis, activation and differentiation. Moreover, mTOR controls the differentiation and functions of Tregs, suggesting that its activity could be targeted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 139 publications
0
102
0
1
Order By: Relevance
“…IL-2/anti-IL-2 Ab complexes have also been used to preferentially promote T reg expansion (40). Modulation of mTOR activity with rapamycin has been shown to promote T reg expansion, survival and function (41). Although no difference in T reg number, proliferation or cytokine production was seen with rapamycin therapy prior to islet transplantation, T regs do have increased suppressive capabilities (42).…”
Section: Boosting Tregs In Mice and Humansmentioning
confidence: 99%
“…IL-2/anti-IL-2 Ab complexes have also been used to preferentially promote T reg expansion (40). Modulation of mTOR activity with rapamycin has been shown to promote T reg expansion, survival and function (41). Although no difference in T reg number, proliferation or cytokine production was seen with rapamycin therapy prior to islet transplantation, T regs do have increased suppressive capabilities (42).…”
Section: Boosting Tregs In Mice and Humansmentioning
confidence: 99%
“…The mTOR and dual PI3K/mTOR inhibitors have been shown to induce Tregs’ expansion and their immunosuppressive activity, thus correlating with a poor prognosis in cancer patients [123]. Encouragingly, Huijts and her group showed that the PI3K inhibition alone allows for the expansion of Tregs, but without affecting their overall suppressive activity [124].…”
Section: Implications In Cancer Immunotherapymentioning
confidence: 99%
“…В составе этих комплексов mTOR является «проводником» как внутриклеточных, так и внеклеточных сигна-лов и служит одним из центральных регуляторов метаболизма, роста, пролиферации и выживания лимфоцитов и других клеток [22], а одним из ее блокаторов является метформин, который дей-ствует через АMPK (AMP-activated protein kinase) [7,13]. Высокая активность mTOR способна уси-ливать прогрессию диабета через активацию эф-фекторных провоспалительных субпопуляций лимфоцитов [26,15], и наоборот, низкая спо-собствует дифференцировке Treg [4,34], блоки-рующих инсулит. Поэтому целью работы было выяснить уровень экспрессии мРНК генов Glut1, mTOR и AMPK1α, а также распределение mTOR + лимфоцитов в ПЛУ крыс с экспериментальным стрептозотоцин-индуцированным сахарным ди-абетом (ЭСИСД) и после введений метформина.…”
Section: Putilin Da Kamyshnyi Am путилин да камышный ам Medunclassified